Exosomes Derived from Gold Nanorod Engineered Vascular Endothelial Cells Inhibit Tumor Growth via Disrupting the TGFβ Pathway. (24th March 2022) - Zhu, Weiye; Zhang, Rui; Zhao, Zichang; Zhao, Na; Gui, Xiao; Cui, Xiao; Shen, Ni; Zhao, Jiawei; Gao, Guangping; Zhang, Haorui; Huan, Chenyang; Zhou, Yukun; et al.
Abstract : Exosomes are nanosized extracellular vesicles which are emerging as novel therapeutic nanoparticles. This paper reports a novel concept of engineering exosomes using nanomaterial inside the vascular endothelial cells (ECs). Gold nanorods (GNRs) could inhibit EC division and internalized GNRs located in endosomes of binucleated ECs. The GNRs could alter the composition of bioactive molecules loaded in exosomes. The engineered EC-derived exosomes could inhibit tumor cell proliferation, migration, and invasion in vitro and suppress tumor growth in vivo. miRNA sequencing showed that the engineered exosomes contained various miRNAs that could disrupt the TGF β pathway. Further data suggested that the engineered exosomes could suppress the expression of TGFβ 1 and TGFβ 2, thus inhibiting the activation of SMAD2 and SMAD3. These data highlighted the therapeutic potential of engineering exosomes using nanomaterials.